Distributed Fusion Estimation for Sensor Networks with Communication Constraints - Zhang, Wen-An.; Chen, Bo.; Song, Haiyu; Yu, Li.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book systematically presents energy-efficient robust fusion estimation methods to achieve thorough and comprehensive results in the context of network-based fusion estimation. It summarizes recent findings on fusion estimation with communication constraints; several novel energy-efficient and robust design methods for dealing with energy constraints and network-induced uncertainties are presented, such as delays, packet losses, and asynchronous information... All the results are presented as algorithms, which are convenient for practical applications.
Introduction -- Multi-Rate Kalman Fusion Estimation for WSNs -- Kalman Fusion Estimation for WSNs with Non-Uniform Estimation Rates -- H1 Fusion Estimation for WSNs with Non-Uniform Sampling Rates -- Fusion Estimation for WSNs Using Dimension Reduction Method -- H1 Fusion Estimation for WSNs with Quantization -- Hierarchical Asynchronous Fusion Estimation for WSNs -- Fusion Estimation for WSNs with Delayed Measurements -- Fusion Estimation for WSNs with Delays and Packet Losses.
Keywords: Control engineering; Signal processing; Telecommunication; Computer networks .; Control and Systems Theory; Signal, Speech and Image Processing; Communications Engineering, Networks; Computer Communication Networks